Functional matching of clothing supplements and their electronically marketed quality (Journal of the College of Basic Education, 2026)
The study aimed to identify the extent to which the functional harmonization of clothing supplements and their quality are electronically marketed and followed the descriptive and analytical approach, as it prepared a questionnaire that included a set of questions in the speaker's form represented by (18) paragraphs, and put alternatives to answering them with (always, sometimes, never), then distributed the questionnaire to female employees and students of Baghdad University, and then statistically analyzed the results as follows: The paragraphs of the questionnaire with the number (18) were taken a paragraph, a percentage weight ranging from (53 -92) % and indicates the answers of the intention towards the acceptability of the questionnaire paragraphs of the questionnaire (above from the middle), and all paragraphs are statistically function, as the values of the square Kai are greater than the tabular values (0.559) at the level (0.059) and Degree of freedom (2), as recorded the results of the Kai box for the answers of the sample on the questionnaire paragraphs to the absence of statistically function differences between the answers for the sample members for paragraph (8) "I think buying through electronic shopping provides more privacy to the consumer."